2020
DOI: 10.1029/2020jd032866
|View full text |Cite
|
Sign up to set email alerts
|

First Lidar Observations of Quasi‐Biennial Oscillation‐Induced Interannual Variations of Gravity Wave Potential Energy Density at McMurdo via a Modulation of the Antarctic Polar Vortex

Abstract: This work presents the first lidar observations of a Quasi‐Biennial Oscillation (QBO) in the interannual variations of stratospheric gravity wave potential energy density (Epm in 30–50 km) at McMurdo (77.84°S, 166.67°E), Antarctica. This paper also reports the first identification of QBO signals in the distance between McMurdo and the polar vortex edge. Midwinter stratospheric gravity wave activity is stronger during the QBO easterly phase when the June polar vortex expands and the polar night jet shifts equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 65 publications
(153 reference statements)
2
9
0
Order By: Relevance
“…According to the aforementioned studies, MJO P7 (P3) leads to a strengthened (weakened) polar vortex. This implies that strengthened (weakened) polar vortex corresponds to enhanced (suppressed) GWs, which is consistent with previous studies (Li et al, 2020; Triplett et al, 2018). Due to the lag of the MJO impacts on the polar vortex, the MJO impacts on GWs in the northern extratropics seem to be delayed accordingly.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to the aforementioned studies, MJO P7 (P3) leads to a strengthened (weakened) polar vortex. This implies that strengthened (weakened) polar vortex corresponds to enhanced (suppressed) GWs, which is consistent with previous studies (Li et al, 2020; Triplett et al, 2018). Due to the lag of the MJO impacts on the polar vortex, the MJO impacts on GWs in the northern extratropics seem to be delayed accordingly.…”
Section: Discussionsupporting
confidence: 92%
“…The strong winds associated with PNJs are important sources of GWs in the winter hemisphere stratosphere (Fritts & Alexander, 2003; Sato & Yoshiki, 2008; Whiteway et al, 1997). In addition, less wind filtering in winter may also explain larger GW variances (Chu et al, 2018; Li et al, 2020; Zhao et al, 2017) than summer. Seasonal maximums are found in the tropics during the summer of each hemisphere (~20°N for JJA and ~20°S for DJF).…”
Section: Observational Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the scope of this work was not to investigate the mechanisms of the QBO-SAM relationship, a possible cause of this link is wave propagation to the stratosphere, which affects the QBO and the polar stratospheric vortex (e.g., Baldwin and Tung, 1994;Thompson and Wallace, 2000;Fogt and Marshall, 2019;Li et al, 2020). The maximum of this wave propagation from the troposphere to the stratosphere in the SH occurs in late spring (Charney and Drazin, 1961;Randel and Newman, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Although it is a tropical phenomenon, the QBO influence on the extratropical regions has been investigated by several authors, mainly in HN (e.g., Tan, 1980, 1982;Baldwin and Tung, 1994;Coughlin and Tung, 2001;Naoe and Shibata, 2010;Kuroda and Yamazaki, 2010;Roy and Haigh, 2011;Anstey and Shepherd, 2014;Li et al, 2020). Holton and Tan (1980) showed that the geopotential height at high latitudes is significantly lower during the westerly QBO phase.…”
Section: Introductionmentioning
confidence: 99%